MIGRASI: ETNISITAS BUDAYA SEBAGAI IDENTITAS BANGSA INDONESIA - Lucas Wattimena (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Migration in Indonesian happening as naturally siklus of life, which is an antrolistik process also sociology interaction culture. Society look deep into the basic concept of culture is natural and is being arismatik. So the identity of ethnic, group, tribe is been important than be all the live of how to live in society, nation and mother land.